Tribute The Road Pavers of Bulgarian Psycholinguistics - Kyuchukov, Hristo (Lesya Ukrainka Eastern European National University, 2024)
In my student years at the beginning of the 1990s at Sofia University, Bulgaria, fate led me to study with two extraordinary scholars – Prof. Dr. Miroslav Yanakiev and Prof. Dr. Encho Gerganov. Prof. Yanakiev laid the foundations of Bulgarian psycholinguistics, introducing the statistical methods in linguistics, and as his student, Prof. Gerganov continued and further developed his ideas. I had the great good fortune to learn from them and consider myself a student of them both. Actually, my scientific and academic activities were launched when I met Prof. Yanakiev, and we sought as a shared task to develop the first ABC textbook in Romani for Roma children in Bulgaria in 1993. Our extensive, strong cooperation continued until the end of Prof. Yanakiev’s life. After his death, I went on working more intensively with Prof. Gerganov, seeking to develop psycholinguistic studies, research and publications with him. Moreover, if I am known for my psycholinguist work today, I owe that in significant measure to my 33 years of collaboration with Prof. Gerganov. This tribute is dedicated to the anniversaries of the two scholars – in 2023 was the 100th anniversary of Miroslav Yanakiev, and in 2024, we celebrate the 85th birthday of Encho Gerganov. Miroslav Yanakiev (19.08.1923 – 09.11.1998), born in Sofia, was deservedly famous worldwide for his works on two Slavic languages: Bulgarian and Russian. In 1943, he graduated from the First Men's High School in Sofia, and the same year, he was enrolled in the Slavic Philology program at Sofia University. He graduated in 1947, and immediately after his graduation, he began work at the Faculty of History and Philology of the same university. He worked there until the end of his life in 1998, first as Assistant Professor, then as Associate Professor and then as Full Professor. In 1963, he earned the title Associate Professor with a habilitation monograph Българско стихознание “Bulgarian Poetics”. In 1979, he was promoted to Full Professor after completing his monograph "Стилистиката и езиковото обучение"/Stylistics and Language Teaching. After his retirement in 1988 and due to our cooperation, he began to work on child bilingualism, mainly with Roma and Turkish children and started publishing articles about the importance of minority mother tongues for the language and cognitive development of children. He was central in supporting my research in the field of Romani language and publishing schoolbooks for Turkish and Roma children. Encho Gerganov was born on March 18, 1939, in the town of Stara Zagora in Bulgaria. He graduated in Bulgarian Philology (specializing in linguistics and mathematical linguistics) at St. Kliment Ohridski University in Sofia. In the period 1968-1972, he was a doctoral student at the Institute of Linguistics of the ASSR in Moscow, where in 1972, he defended a dissertation entitled "Некоторые закономерности зрительного распознавания элементов текста" / Some Regularities of the Visual Recognition of Text Elements. Prof. Gerganov began his academic career at the Institute for Foreign Students in Sofia (1967-1989), where in 1977, he was granted the title Associate Professor earned with a habilitation monograph Психометрични методи за проверка и оценка на знанията по български език (Psychometric Methods for Testing and Assessment of Knowledge in Bulgarian Language). In 1988, he was promoted to Full Professor in recognition of his monograph "Памет и смисъл"/Memory and Meaning. From 1984 to 1988, Prof. Gerganov was the Institute's Deputy Rector. From 1989-2000, he worked at the Institute of Psychology of the Bulgarian Academy of Sciences, where from 1991 to 2000, he headed the section on cognitive psychology and research methods, and from 1991 to 1995, he was the Director of the Institute. Prof. Gerganov was Deputy Minister of Public Education (1991-1992) and Director of the National Test Center (1994-1995). Professor Encho Gerganov was one of the first professors at the New Bulgarian University (NBU) and the first head of the Cognitive Science and Psychology Department (1992–2002) there. In 2009, he was awarded the title "Doctor Honoris Causa” by the Constantine the Philosopher University, Nitra, Slovakia. Together with Prof. Gerganov, we carried out many studies and co-authored numerous articles focused on Romani-Bulgarian and Turkish-Bulgarian bilingualism in Bulgaria. In 1999, we co-authored a monographic study: Герганов, E. и Кючуков, Хр. (1999). Oбразователни нагласи на ромите в България. София: Тилия / Gerganov, E. & Kyuchukov, H. (1999). Educational Attitudes of Roma in Bulgaria. Sofia: Tilia. With his outstanding and pioneering work and research, I am confident that Prof. Gerganov brought the educational issues of minority children in Bulgaria to a higher scientific level. Professors Miroslav Yanakiev and Encho Gerganov deeply dedicated their academic lives to linguistics and psycholinguistics. Through their studies, research, and publications, they helped to change the lives of many in Bulgaria and Europe.